ANALYSIS OF THE EFFECTIVENESS OF PEDESTRIAN CROSSING BRIDGE (JPO) FACILITIES IN BANJARBARU CITY - Fadhilah, Erwin Rony; Widayanti, Nova (CERUCUK, 2026)
People crossing bridges serve as a means to reduce conflicts between pedestrians and vehicles, which can interfere with the smooth flow of traffic, as well as improve safety and comfort when crossing. One of the roads in Banjarbaru that uses access to cross people, namely on Ahmad Yani KM 34 street, precisely adjacent to the Banjarbaru City BNI office. This pedestrian crossing bridge is newly built by the government, this is done based on consideration of the need for transportation crossing facilities/infrastructure in the city of Banjarbaru. This study was conducted to evaluate the performance of the use of pedestrian bridges in Banjarbaru City by considering the frequency of crossings (P), traffic intensity (V), and evaluations from participants. The level of effectiveness of the use of pedestrian bridges is classified as "highly effective." Based on the results of the analysis, the PV2 value  obtained exceeded 2x108. The number of crossers (P) is in the range of 50-100 people per hour, while the volume of vehicles (V) is in the range of >750 vehicles per hour. Referring to the standards of the Directorate General of Highways in 2023, the most suitable crossing facility for the location being studied is Pelican with waiting stalls and pelican only. Based on the assessment of pedestrians using the Likert scale, a total average score of 3.085 was obtained, which shows that its effectiveness is relatively low. Based on observations and measurements at the site, several parameters were found that did not meet the applicable guideline standards. For example, the height of the climb (0.1 m) is less than the stipulated (it should be a minimum of 0.15 m and a maximum of 0.18 m). In addition, the width of the step (0.25 m) is not in accordance with the Bina Marga regulations which require a minimum width of 0.3 m. And the ramp width does not meet. Keywords : Pedestrian, Effectiveness, Crossing Facilities